Family Connections randomized controlled trial: assessing the feasibility and acceptability of an intervention with adolescents living with HIV and their caregivers in Ndola, Zambia. Issue 4 (3rd April 2022) - Denison, Julie A.; Packer, Catherine; Nyambe, Namakau; Hershow, Rebecca B.; Caldas, Stephanie; Miti, Sam; Sudarsan, Swati; Chen, Mario; Bernholc, Alissa; Mwansa, Jonathan K.; McCarraher, Donna R.
ABSTRACT: Achieving the 95-95-95 UNAIDS targets requires meeting the needs of adolescents, however we lack evidenced-based approaches to improving adolescent adherence to antiretroviral therapy (ART), increasing viral suppression, and supporting general wellbeing. We developed Family Connections as a group intervention for adolescents and their adult caregivers and conducted a randomized controlled trial in Ndola, Zambia to test feasibility and acceptability. Fifty pairs ( n = 100) of adolescents (15–19 years and on ART ≥ 6 months) and their caregivers were randomly assigned either to the intervention consisting of 10 group sessions over 6 months, or to a comparison group, which received the usual care. Each pair completed baseline and endline surveys, with adolescents also undergoing viral load testing. Of the 24-intervention adolescent/caregiver pairs, 88% attended at least eight group sessions. Most adolescents (96%) and all caregivers would recommend Family Connections to peers. Adolescent viral failure decreased but did not significantly differ by study group. Adolescents in the intervention group showed a greater reduction in HIV-related feelings of worthlessness and shame than the comparison group. The feasibility, acceptability, and the positive trend toward significantly reducing internalized stigma, generated by this Family Connections pilot study, contributes valuable data to support adolescent/caregiver approaches that use peer groups.